Is place of birth associated with mode of birth? The effect of hospital on caesarean section rates in a public metropolitan health service. (13th November 2013) - Biro, Mary A.; Knight, Michelle; Wallace, Euan; Papacostas, Kerrie; East, Christine
<x xml:space="preserve">Abstract</x> Background The effects of place of birth on birth outcomes have been examined in several studies both locally and internationally. However, none has examined the impact on caesarean section rates of different level maternity hospitals operating within the one health service. This study aimed to examine the impact of place of (Hospital level 6; 4–5 or 4) on birth outcomes in a large metropolitan health service in Victoria. Methods A cross‐sectional study utilising data on births to low‐risk first‐time mothers during 2010–2011. Data were obtained from the Birthing Outcome System (BOS) database of Monash Health. Unadjusted and adjusted analyses were undertaken using logistic regression to examine the association between place of birth and caesarean section. Results In this group of low‐risk nulliparae, there was evidence of a significant association between place of birth and caesarean section. The lower the acuity of the hospital, the higher the odds for the caesarean section. Compared with the level 6 hospital, the AdjOR for caesarean section at the level 4 hospital was 1.81 (95% CI: 1.37–2.41) and at the level 4–5 hospital, 1.30 (95% CI: 1.0–1.7). Conclusions Low‐risk nulliparae in spontaneous labour giving birth at the level 4 hospital in this health service are at significantly increased risk of caesarean section. This may have implications for the organisation and resource management of other level 4 public maternity units. Care in a tertiary (level 6) service may not necessarily equate to the higher rates of intervention reported by others.